2019
DOI: 10.3390/v11010035
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Arboviral Infection in Mice Lacking the Interferon Alpha/Beta Receptor

Abstract: Arboviruses are arthropod-borne viruses that exhibit worldwide distribution and are a constant threat, not only for public health but also for wildlife, domestic animals, and even plants. To study disease pathogenesis and to develop efficient and safe therapies, the use of an appropriate animal model is a critical concern. Adult mice with gene knockouts of the interferon α/β (IFN-α/β) receptor (IFNAR(−/−)) have been described as a model of arbovirus infections. Studies with the natural hosts of these viruses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 168 publications
(182 reference statements)
2
32
0
Order By: Relevance
“…Even if it has been shown that ATA has in vitro inhibitory activity against multiple RNA or DNA viruses [ 35 , 45 , 46 , 47 , 48 , 51 , 53 , 54 , 55 , 56 , 57 , 58 ], its antiviral efficacy in in vivo models has not been demonstrated [ 58 ], and there is a limited number of studies showing the effect of ATA in vivo [ 41 , 59 , 60 ]. Therefore, prior to conducting antiviral experiments in IFNAR (−/−) mice, a well-accepted mouse model to study BTV and AHSV infections [ 61 , 62 ], the effect of ATA in this animal model was assessed. For that, three groups of animals were treated daily for eight days with 600 µg of ATA diluted in PBS, DMSO diluted in PBS, or PBS.…”
Section: Resultsmentioning
confidence: 99%
“…Even if it has been shown that ATA has in vitro inhibitory activity against multiple RNA or DNA viruses [ 35 , 45 , 46 , 47 , 48 , 51 , 53 , 54 , 55 , 56 , 57 , 58 ], its antiviral efficacy in in vivo models has not been demonstrated [ 58 ], and there is a limited number of studies showing the effect of ATA in vivo [ 41 , 59 , 60 ]. Therefore, prior to conducting antiviral experiments in IFNAR (−/−) mice, a well-accepted mouse model to study BTV and AHSV infections [ 61 , 62 ], the effect of ATA in this animal model was assessed. For that, three groups of animals were treated daily for eight days with 600 µg of ATA diluted in PBS, DMSO diluted in PBS, or PBS.…”
Section: Resultsmentioning
confidence: 99%
“…Type I interferon receptor defective mice (IFNAR (-/-)) on a 129 Sv/Ev background [ 42 ], and sheep (Spanish “Churra” sheep breed), were used for the studies. Mice and sheep were housed under pathogen-free conditions and allowed to acclimatize to the biosafety level 3 (BSL3) animal facilities at the Animal Health Research Center (INIA-CISA), Madrid, before use.…”
Section: Methodsmentioning
confidence: 99%
“…Immune responses induced by dual MVA against proteins of RVFV and BTV in mice A number of experimental vaccines for BTV and RVFV have been previously studied in the mouse model based on IFNAR (−/−) mice [22][23][24][25][26][27][28] . Although extrapolation of findings in mice to natural hosts must be done with care due to differences in the biology between mouse and ruminants, experimental infections of IFNAR (−/−) mice with several studied arboviruses, such as BTV and RVFV closely mimics hallmarks of these viruses in their natural host 29 .…”
Section: Expression Of Heterologous Proteins By Mva Vectorsmentioning
confidence: 99%